Assessing the Effect of Groundnut Shell Ash-Lime Stabilization of Reclaimed Asphalt Pavement for Road Construction. - Tumusiime, Innocent (Kabale University, 2025)
Pavement rehabilitation and reconstruction generate large quantities of reclaimed asphalt pavement (RAP) and recycling into new asphalt paving mixtures is the predominant application. RAP acceptance in road bases and subbases has been limited, because of the lack of laboratory and field performance data while large quantities of groundnut shell ash (GSA) are generated from the combustion of groundnut shell and also disposed in large quantities on production sites and production of Lime not only imposes financial burdens but also contributes to environmental degradation and carbon emissions. This paper presents the results of the laboratory evaluation of the characteristics of GSA-Lime stabilized RAP with a view of determining its suitability for use as highway pavement material in flexible pavement construction. An X-ray fluorescence test was conducted on GSA to determine the chemical composition. Preliminary tests (Natural moisture content, Particle size distribution, and Atterberg limit) and engineering tests (compaction and California bearing ratio (CBR)) were conducted on the RAP samples in their natural state. (GSA +Lime) was then added to the RAP at 5, 10, 15 and 20% proportions. Atterberg limits, compaction, and CBR tests were conducted for each addition of (GSA +Lime). The RAP - (GSA +Lime) mixtures were subjected to British Standard (BS Heavy) compaction effort to determine the compaction characteristics and California bearing ratio (CBR). Test results show that the properties of RAP improved with GSA-Lime treatment. RAP was classified as A-1-a using the AASHTO classification system and the general rating as sub-grade in accordance with AASHTO (1986) is excellent too good. The values of Maximum dry density (MDD) increased from 1.894 and 2.016 g/cm3 at 5% and 10% (GSA +Lime) treatment respectively and decreased furthermore with an increase in the percentage of (GSA +Lime) while the optimum moisture content (OMC) increased with increase in (GSA +Lime) content in the RAP - (GSA +Lime) mixes. The test results show that there was a decrease in the liquid limit ranging from 34.5% to 31.2% at 0% and 20% (GSA +Lime). The CBR values increased at 5% and 10% (GSA +Lime) treatment from 2.6% at 0% to 20% and 49% respectively at 95% degree of compaction and from 2.8% at 0% to 22% and 65% respectively at 98% degree of compaction and values of CBR reduced with further increase in the percentage of (GSA +Lime). Optimum stabilization was obtained at 10% (GSA +Lime) where CBR values of 49% and 65% at 95% and 98% degrees of compaction respectively. This optimum mix (GSA +Lime) is suitable for use in the construction of the G45 Subbase layer and G60 Base course layer in road construction according to Uganda MoWH&C (2005). This research provides the results of the evaluation of (GSA +Lime) stabilized RAP as highway construction material, as it is based on CBR determination. Further studies can be conducted to evaluate the effectiveness of different types of lime like quicklime.